Impact of non-thermal plasma treatment on the seed germination and seedling development of carrot (Daucus carota sativus L.). (23rd December 2021) - Guragain, Rajesh Prakash; Baniya, Hom Bahadur; Pradhan, Suman Prakash; Dhungana, Santosh; Chhetri, Ganesh Kuwar; Sedhai, Binita; Basnet, Niroj; Panta, Gobinda Prasad; Joshi, Ujjwal Man; Pandey, Bishnu Prasad; Subedi, Deepak Prasad
Abstract: Seed germination is a complicated physiological process that starts with the seed absorbing water and concludes with the radicle emerging. The kinetics and amount of water uptake by seeds are known to be influenced by both seed surface properties and the surrounding environment. As a result, altering seed surface features are linked to seed medium and is a valuable strategy for controlling seed germination. In the agricultural field, non-thermal plasma surface activation of seeds is currently being investigated as an efficient pre-sowing treatment for modifying seed germination. The impact of non-thermal plasma (NTP) on the germination and seedling growth of carrot seeds at room temperature and atmospheric pressure for varied treatment times was investigated in this study. Seed's germination properties and growth parameters were examined for both control and NTP-treated seeds. Germination-related parameters such as germination percentage, vigor index, and chlorophyll content were all improved by NTP treatment. However, no significant changes were seen in the carotenoid content. Similarly, the in-vitro radical scavenging activities, total phenol, and total flavonoid contents in the seedlings were altered by NTP treatment. Our results indicate that NTP treatment has a favorable effect on carrots germination and seedling development.